2018
DOI: 10.1002/jctb.5661
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 5‐(Aminomethyl)‐2‐furanmethanol by direct reductive amination of 5‐Hydroxymethylfurfural with aqueous ammonia over the Ni/SBA‐15 catalyst

Abstract: BACKGROUND 5‐(Aminomethyl)‐2‐furanmethanol (AMF), used widely in medicinal chemistry, is usually synthesized by the reductive amination of furfural or 5‐hydroxymethylfurfural (HMF) with ammonia. However, a challenging task when synthesizing this furyl primary amine is to enhance the selectivity of the product due to its high nucleophilicity. Conventional measures have used excessive liquid ammonia and precious metal catalysts. Usually, the molar ratio of ammonia to substrate is up to 30:1. This study employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…Analogous to furfural, reductive amination of HMF constitutes a significant fundamental route for the sustainable production of N-containing compounds from renewable biomass. Some of the reported literatures also suggested that the reactivity of HMF in the reductive amination with gaseous or aqueous ammonia was superior to furfural in terms of target yield and reaction conditions 21,22,40 , in according with our results in Entry 39 and 41. Other kinds of biomass-derived platforms such as phenolic model monomers (e.g., phenol and substituted phenol) derived from lignin were also tolerated in our experiments (Entry 46-61).…”
Section: Substrate Scope and The Reaction Mechanismsupporting
confidence: 87%
“…Analogous to furfural, reductive amination of HMF constitutes a significant fundamental route for the sustainable production of N-containing compounds from renewable biomass. Some of the reported literatures also suggested that the reactivity of HMF in the reductive amination with gaseous or aqueous ammonia was superior to furfural in terms of target yield and reaction conditions 21,22,40 , in according with our results in Entry 39 and 41. Other kinds of biomass-derived platforms such as phenolic model monomers (e.g., phenol and substituted phenol) derived from lignin were also tolerated in our experiments (Entry 46-61).…”
Section: Substrate Scope and The Reaction Mechanismsupporting
confidence: 87%
“…Classical methods of reductive amination with borohydrides as reducing agents afford furanic amines 18 via formation of imine intermediates [48] . The same outcome can be achieved with more environmentally friendly transition metal‐catalyzed [27,45a,e,49] or biocatalyzed [50] methodologies.…”
Section: Ab‐type Furanic Building Blocksmentioning
confidence: 77%
“…5‐(Aminomethyl)‐2‐furanmethanol (AMF) containing both hydroxymethyl and aminomethyl groups at the furan ring is one of the most important aminated HMF‐derived building blocks with enormous synthetic potential. AMF can be prepared in good yields by reductive amination of HMF with ammonia in the presence of hydrogen by using either transition metal catalysts [45e,49a,b,f,51] or biocatalytic methods [45e,50,52] . Amination of AMF affords important monomer 2,5‐bis(aminomethyl)furan (BAMF) [49a] or other furanic amines including biologically active compounds [53] .…”
Section: Ab‐type Furanic Building Blocksmentioning
confidence: 99%
“…HMF has been identified as one of the most important biomassbased platform chemicals, because it can be transformed into many value-added chemicals. [1][2][3][4][5][6][7] HMF can be obtained from lignocellulose derivatives. 1,2 For the conversion of abundant and cheap fructose-based biomass into HMF or its derivatives, the activity of the catalyst and the reaction media can greatly influence fructose conversion and product selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…HMF has been identified as one of the most important biomass‐based platform chemicals, because it can be transformed into many value‐added chemicals 1–7 . HMF can be obtained from lignocellulose derivatives 1,2 .…”
Section: Introductionmentioning
confidence: 99%